Sustainable rural economies, evolutionary dynamics and regional policy. (January 2018) - Plummer, Paul; Tonts, Matthew; Argent, Neil
Highlights: Application of evolutionary economic geography to understanding restructuring in Australian rural economies. Restructuring contributed to major economic upheaval in rural economies. Local policy interventions have been numerous though have not altered long term development trajectory of rural economies.